Aprendendo a ensinar: a contribuição das disciplinas didática e didáticas específicas para a formação de professores no Curso de Pedagogia da Unimontes (2013 -2017) - Brito, Denice do Socorro Lopes (2018)
The purpose of this study was to analyze the contributions of Didactics and Specific Didactics to the training of teachers who will work in the initial years of Elementary School, which is an opportunity for the Pedagogy course at Unimontes, an institution located in the Northern region of Minas Gerais. As a problem questionnaire, the questionnaire asked the question of the extent to which the proposals of Didactics subjects include the formative presuppositions, defined for the pedagogical activity, as a teacher, by the Curricular Guidelines who started to standardize the course of Pedagogy in 2006. In addition, we sought to understand the ways of referring those proposals, in the effective process of training of future teachers, from the voices of the subjects involved in the process, that is, teacher trainers and students. From a methodological point of view, a bibliographical, documentary and field research work was undertaken, which, in turn, allowed the construction of several analytical categories. Among the possibilities were chosen five categories that, built relationally, allowed a dialogue, including the other reflective possibilities offered by the data found: Didactic knowledge: reflections on the didactic discipline; Didactics and specific didactics: a field of (dis) meetings ?; Relations between didactic knowledge and specific methodologies: subjects' perceptions; Unit theory-practice: developing pedagogical praxis; Formative practices: possibilities of development of the relation theory and didactic practices. Among the results found, the study showed that there is a tendency of the teachers to treat the Didactic and Specific Didactics disciplines prioritizing their technical dimension. Paradoxically, the reading offered by the students gives account of a distance from the technique, of studies that are too theoretical, disjointed and separated from the reality that is found in the daily school life.